Sistem Pakar Berbasis Web Dalam Penentuan Pemilihan Jurusan Vokasi menggunakan Metode Certainty Factor - Rahmat Widia Sembiring; Ramadhanu Ginting; Rizky Maulidya Afifa; Fristi Riandari; Afrisawati Afrisawati (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2025)
The selection of a study program in higher vocational education is a crucial stage that can determine the future career development of students. In practice, many high school and vocational school graduates still face difficulties in choosing a program that aligns with their interests, talents, and potential. This research presents the design and implementation of a web-based expert system that serves as a decision-support tool for recommending vocational study programs by applying the Certainty Factor method. The Certainty Factor method is employed to measure the level of expert confidence in the facts or criteria provided by users, thereby generating a degree of certainty in the recommendation process. The system is developed with a web-based interface to ensure broad accessibility, ease of use, and interactivity for students. The experimental results indicate that the proposed expert system can assist in mapping students’ program preferences more objectively and systematically based on their individual characteristics. Therefore, this system is expected to serve as an alternative decision-support instrument in determining vocational study programs and contribute to improving the accuracy of educational pathway selection in accordance with students’ potential.